2006
DOI: 10.1099/mic.0.28729-0
|View full text |Cite
|
Sign up to set email alerts
|

ThHog1 controls the hyperosmotic stress response in Trichoderma harzianum

Abstract: Trichoderma harzianum is a widespread mycoparasitic fungus, able to successfully colonize a wide range of substrates under different environmental conditions. Transcript profiling revealed a subset of genes induced in T. harzianum under hyperosmotic shock. The hog1 gene, a homologue of the MAPK HOG1 gene that controls the hyperosmotic stress response in Saccharomyces cerevisiae, was characterized. T. harzianum hog1 complemented the hog1D mutation in S. cerevisiae, but showed different features to yeast alleles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 53 publications
1
56
0
Order By: Relevance
“…Expression of the hydrophobin-encoding genes hyd1 and hyd2 in the ⌬Bbhog1 mutant and the wild-type strain. Real-time RT-PCR was used to determine the relative levels of expression of hyd1 and hyd2 using Bgpd, ␤-tubulin, and 18S rRNA as loading controls to normalize samples by a method described previously (52) (11). Here we found that Bbhog1 was an important virulence determinant of B. bassiana and influenced at least three aspects of infection, spore viability, adherence to the insect cuticle, and appressorium formation.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Expression of the hydrophobin-encoding genes hyd1 and hyd2 in the ⌬Bbhog1 mutant and the wild-type strain. Real-time RT-PCR was used to determine the relative levels of expression of hyd1 and hyd2 using Bgpd, ␤-tubulin, and 18S rRNA as loading controls to normalize samples by a method described previously (52) (11). Here we found that Bbhog1 was an important virulence determinant of B. bassiana and influenced at least three aspects of infection, spore viability, adherence to the insect cuticle, and appressorium formation.…”
Section: Discussionmentioning
confidence: 75%
“…For instance, deletion of HOG1-encoding genes in Candida albicans (44), Neurospora crassa (58), Magnaporthe grisea (12), and Colletotrichum lagenarium (29) causes a defect in adaptation to highosmolarity conditions. A hog1-silenced strain of Trichoderma harzianum was highly sensitive to osmotic stress and showed intermediate levels of sensitivity to oxidative stress (11). HOG1 MAP kinase is activated by high osmolarity, oxidative stress, and UV stress in Debaryomyces hansenii (47).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In Saccharomyces cerevisiae, the main pathway involved in sensing changes in Na ϩ concentrations and in responding to them is known as the HOG signaling pathway, which controls the expression of others osmoresponsive genes. The hog1 gene homologue was isolated and characterized from T. harzianum (5) and was shown to be important for the hyperosmotic stress response but also for fungus-fungus interactions.…”
Section: Discussionmentioning
confidence: 99%